Study of the effect of laboratory-simulated ageing on the damage resistance of polymer-modified bitumens in intermediate climates - Cuciniello, Giacomo (2019)
Polymer additives are widely used to improve the performances of road bitumens. However, although their advantages are well recognised, there are still drawbacks and concerns that limit the widening of their usage. One of these concerns is the lack of understanding of their ageing-inhibitor properties.